TINJAUAN YURIDIS TERHADAP TINDAK PIDANA KESUSILAAN ANAK DAN PENYELESAIANNYA MENURUT SIYASAH DUSTURIYAH (Studi Kasus Putusan Hakim Pengadilan Negeri Tasikmalaya Perkara No : 4/Pid.Sus-Anak/2021/PN Tsm) - Muhammad Zidan; A. Arsyul Munir, Asep; Ecep Nurjamal; Munir, Asep (Siyasyatuna | Jurnal Hukum Tata Negara, 2024)
Criminal acts of decency committed by children are of course different from criminal acts committed by adults. Found in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, this shows that legal institutions in Indonesia are very concerned about the protection and rights of children, both victims and perpetrators. The purposes of this research are: 1) To find out the criminal procedural law that was carried out by judges at the Tasikmalaya District Court in dealing with criminal acts of decency committed by children. 2) To find out the verdict on the result of the crime of a child who committed a crime of decency at the Court Decision number PN TASIKMALAYA Number 4/Pid.Sus- Anak/2021/PN Tsm. 3) To find out the settlement of child decency crimes according to the siyasah dusturiyah perspective. The method used in this study is normative juridical through the Statute Approach, namely examining all regulations and laws concerned with related research. In the case with No. 4/Pid.Sus-Children/2021/PN Tsm, the perpetrator's child was not detained but received guidance in the Institution for 1 (one) year and Job Training for 6 (six) months, at the Social Welfare Organizing Institution (LPKS) in I'Anatush Syibiyan in the Hamlet area of Babakan RT. 01, R.W. 01, Sindangjaya Village, Mangunjaya District, Pangandaran Regency. As well as being burdened with paying court fees in the amount of Rp. 2,500.00 (Two thousand five hundred rupiah).